EFEKTIFITAS DAN KENYAMANAN TRANSCUTANEUS ELECTRICAL NERVE STIMULATION ( TENS ) PULSE BURST DAN ARUS TRABERT DALAM MENGURANGI NYERI KRONIK DI LUTUT PADA USIA LANJUT - WIDIYASARI, WIWIK (2009)

(untitled)
TENS suggested for disease at older person with muskuloskeletal chronic pain especially in knee. Purpose of the research to know effectiveness and comfort TENS pulse burst and trabert flow in decrease chronic pain in knee at older person. Place of this research is executed in building main older person Aisyiyah of Surakarta City during one month. Research method is quasi experimental to know an intervention or treatment at research object. Sample consisted of 4 person at group of TENS pulse burst and 4 person at group of trabert flow. As data analysis with Paired Sample T test and One Way Anova to know influence of treatment and to know difference activity between two treatment. Conclusion taken away from by research is there are effectiveness level of TENS pulse burst to decrease chronic pain in knee at older person ( p = 0, 004 ). There is pleasure level of trabert flow to decrease chronic pain in knee at older person ( p = 0, 023 ). There by therapy method of TENS pulse burst more effective to give at older person to decrease chronic pain in knee.